Potential of Polysulfone/Polydimethyl Siloxane Thin Film Composite (PSf-PDMS-TFC) Membrane for CO2/N2 Gas Separation - Sunarti, Abd Rahman; Nur Atikah, Che Embee; Abdul Latif, Ahmad; Hasrinah, Hasbullah (IOP Publishing, 2018)
The capture and storage of carbon dioxide has been identified as one potential solution to greenhouse gas driven climate change. Efficient separation technologies are required for removal of carbon dioxide from flue gas streams to allow this solution to be widely implemented. This study is mainly focusing on the effect of different concentration of polydimethyl siloxane (PDMS) in dip-coating solution on the membrane's performance. The asymmetric thin flat sheet membrane was prepared by dry / wet phase inversion process consisting 20 %w/v of polysulfone (PSf) as the support layer polymer and 80 %w/v of N-methyl-2-pyrrolidone (NMP) as the solvent. PDMS was coated on the support PSf membrane with the composition of 10, 15 and 20 wt% of PSf in n-hexane respectively. The characterization of morphology of TFC membrane will be conducted by using Scanning Electron Microscopy (SEM) and Fourier Transform Infrared (FTIR). The membrane's performance and the selectivity of CO2/N2 separation will be determined by conducting gas permeation test. The result obtained, show that membrane with highest concentration of PDMS in dip-coating solution give a highest performance in selectivity and unfortunately it contributes to lower permeability. It is vice versa from the membrane without PDMS in the top layer which gives highest value of permeability but lowest in selectivity. From the characterization and permeation test of the membrane, hereby the membrane with highest percentage of PDMS should be selected for the future development of membrane due to its highest value of selectivity which contributes to highest efficiency in separating the gas.